Edukasi Bahaya Investasi Ilegal Dan Pinjaman Online Ilegal Di Deli Serdang Kecamatan Patumbak - Joharsah, Joharsah; Ikhwan, Hablil (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
The rapid development of financial technology (fintech) in Indonesia has brought serious challenges, specifically the proliferation of illegal investment and online lending schemes that cause public unrest. This community service activity aims to provide education and improve financial literacy for residents in Patumbak District, Deli Serdang Regency, to prevent material and non-material losses resulting from illegal financial practices. The primary issue identified at the partner location was a low understanding of the legality of financial institutions and a lack of awareness regarding personal data protection, which is frequently exploited by illegal debt collectors through intimidating actions. The method employed in this service is a descriptive qualitative approach involving socialization stages, interactive discussions, and practical assistance based on the